Advances in Nucleic Acid Detection and Quantification. (6th May 2009) - Kavanagh, Ian C.; Baker, Simon C.
Abstract : The last decade has seen many changes in molecular biology at the bench, as we have moved away from a primary goal of cataloguing genes and mRNA towards techniques that detect and quantify nucleic acid molecules even within single cells. With the invention of the polymerase chain reaction (PCR), a nucleic acid sequence could now be amplified to generate a large number of identical copies, and this launched a new era in genetic research. PCR has developed in parallel to fluorescent hybridization probing to provide low-, medium- and high-throughput detection methods. However, PCR and hybridization detection have significant drawbacks as long-term solutions for routine research and diagnostics assays. Therefore many novel methods are being developed independently, but as yet no one technique has emerged as a clear replacement for PCR, microarrays or even sequencing. In order to examine the technological horizon in this area, around 90 delegates assembled at Hinxton Hall, Cambridge, U.K. on 28 and 29 October 2008 for a Biochemical Society/Wellcome Trust Focused Meeting sponsored by Thermo Fisher Scientific and the British Library. The title of the meeting was 'Advances in Nucleic Acid Detection and Quantification', and the primary aim was to bring together scientists from different disciplines who nevertheless are trying to develop reliable methods for the quantification or detection of RNA and DNA molecules. This meant that physical and organic chemists, microbial ecologists and clinicians appeared alongside molecular biologists. An introductory session on general nucleic acid detection technologies was initiated with a fascinating insight into single-molecule, singlecell hybridization from Professor Sir Edwin Southern. This served as an ideal base for sessions on single-cell molecular biology and an examination of current applications of emerging technology. This issue of Biochemical Society Transactions contains some of the papers prepared by speakers at the meeting, and highlights not only how PCR and microarrays are already being replaced, but also which methods are likely to replace them.